2018
DOI: 10.3389/fpubh.2018.00049
|View full text |Cite
|
Sign up to set email alerts
|

Perceived and Personal Mental Health Stigma in Latino and African American College Students

Abstract: Mental health stigma occurs when people have negative thoughts and beliefs of those with mental health illnesses or mental health treatment. Mental health stigma is related to an assortment of negative outcomes including discrimination in housing and employment, reduced usage of mental health services, and poor mental health outcomes. These implications may be particularly salient for ethnic minorities such as African Americans and Latinos who already suffer from other types of discrimination. This study exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
52
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(62 citation statements)
references
References 61 publications
0
52
1
1
Order By: Relevance
“…Several studies have found that Blacks associate higher levels of stigma with mental illness than Whites. [34][35][36][37] Parents who hold stigmatizing views of mental illness are less likely to acknowledge that their child has a mental health problem and also may attempt to protect their child from being labeled. 38 In addition, studies have documented that Black cultural values of personal strength and addressing problems within the family or through religious practices may view seeking professional help for mental health problems as a sign of weakness.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have found that Blacks associate higher levels of stigma with mental illness than Whites. [34][35][36][37] Parents who hold stigmatizing views of mental illness are less likely to acknowledge that their child has a mental health problem and also may attempt to protect their child from being labeled. 38 In addition, studies have documented that Black cultural values of personal strength and addressing problems within the family or through religious practices may view seeking professional help for mental health problems as a sign of weakness.…”
Section: Discussionmentioning
confidence: 99%
“…DeFreitas et al . 2018). The caregiving burden and experiences of Hispanic/Latinx caregivers may be compounded by these contextual variables, which may contribute to increased support needs (Blanche et al .…”
Section: Introductionmentioning
confidence: 99%
“…Mental health stigma can be conceptualized in a variety of ways, and it has usually been classified as perceived stigma and personal stigma. Perceived stigma concerns negative attitudes where one believes that society as a whole holds about individuals with mental illness, while personal stigma focuses on one’s own beliefs about individuals with mental illness (8). Stigma emerged as an important barrier to the treatment of depression and other mental illnesses.…”
Section: Introductionmentioning
confidence: 99%